1965
DOI: 10.1007/bf00038987
|View full text |Cite
|
Sign up to set email alerts
|

The utility of hill plots in oat research

Abstract: From 1955 through 1963, approximately 300,000 hill plots have been used in various experiments in the Iowa small grain research program. When grain yield, plant height, and heading date were measured on the same varieties, the genetic correlations between rod rows and hills were 0.98, 0.96 and 0.96, respectively.The coefficients of variation for plant height, weight per volume, spikelets per panicle, panicles per plant, weight per 100 seeds were similar for rod rows and hills. However, the coefficients of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
2

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 19 publications
4
31
0
2
Order By: Relevance
“…Plant Sci, 52:735-742 (Sept, 1972) Other studies on wheat grain protein content have revealed heritabilities ranging from 15 to I03% (Kaul and Sosulski 1965;Lofgren et al 1968;Sunderman et al 1965). Frey et al (1955) (Frey 1965 Heritability percentages from regressing F" offspring on F, parents ranged from …”
Section: Introductionmentioning
confidence: 99%
“…Plant Sci, 52:735-742 (Sept, 1972) Other studies on wheat grain protein content have revealed heritabilities ranging from 15 to I03% (Kaul and Sosulski 1965;Lofgren et al 1968;Sunderman et al 1965). Frey et al (1955) (Frey 1965 Heritability percentages from regressing F" offspring on F, parents ranged from …”
Section: Introductionmentioning
confidence: 99%
“…(Walsh etal. 1976), oats (Frey 1965) and both common and durum wheats (Baker and Leisle 1970 (Frey 1965) and barley (Welty and Ramage 1973) (Frey 1965;Baker and Leisfe 1970; Walsh et al 19'16;Garland and Fehr 1981).…”
mentioning
confidence: 99%
“…(Smith et al 1970), unfair ranking of cultivars using mean yields (Baker and Leisle 1970), or insufficient replication (Walsh et al 1976 Frey (1965) and Walsh et al (1976). As is apparent in the computational formula presented in Materials and Methods, this statistic requires estimation of genetic parameters also used in computing heritabilities.…”
mentioning
confidence: 99%
“…Frey (1965) (Table 3). Baker and Leisle (1970) pointed out the weaknesses of comparing methods based on phenotypic correlations.…”
mentioning
confidence: 99%